Հորացիոյի կերպարի մեկնաբանությունը՝ որպես հին հունական քորոսի ղեկավար - Արա Երնջակյան (ՀՀ ԳԱԱ հրատ.)
In this article Horatio’s role from Shakespeare’s drama < < Hamlet > > is being studied. It should be noted that none of the Shakespeare’s predecessors had a hero whose role would be to pass on to the next generations the tragedy of the Ellsinore castle. This brings forth the version that Horatio takes up the role of the chorus from the ancient Greek chorus.
Keywords: Language and Literature; Dramatic representation; The Theater